The Effect of Curcuma Longa Rhizome Extract on the Root Canal Dentin Discoloration - Aulia Azzahra; Rini Bikarindrasari; Martha Mozartha (Insisiva Dental Journal: Majalah Kedokteran Gigi Insisiva, 2022)
Root canal treatment aims to remove vital and necrotic tissue, microorganisms, and their products from the root canal. In this case, chemical endodontic irrigants such as NaOCl and Chlorhexidine (CHX) are required. Unfortunately, both have side effects. Twenty percent of C. longa rhizome extract may be a potential alternative due to its antibacterial activity and the ability to dissolve the smear layer. However, it contains curcumin, a colorant that can stain dentin. This study aims to evaluate the influence of 20% C. longa rhizome extract on root canal dentin discoloration. Thirty decoronated incisor root segments were prepared using the crown-down technique and divided into three groups (n=10). Each group was irrigated with a different solution. Twenty percent of C. longa rhizome extract was the treatment group, the combination of 5.25% NaOCl and 2% CHX was the positive control group, and distilled water was the negative control group. UV Vis 2401 PC spectrophotometer was utilized based on the dE*ab value to assess the discoloration on the root canal. The One Way ANOVA and Post Hoc Games Howell tests were employed to analyze the data. The highest discoloration value was revealed in the treatment group, and the least was in the negative control group, with a significant difference between the two. Furthermore, One-way ANOVA showed no significant differences between the treatment and positive control group (p0.05). C. Longa 20% extract had an effect on the discoloration of root canal dentin.